The golden hour : a novel - Williams, Beatriz (New York : William Morrow, an imprint of HarperCollinsPublishers, 2019)
"The Bahamas, 1941. Newly-widowed Leonora (3z(BLulu(3y (BRandolph arrives in Nassau to investigate the Governor and his wife for a New York society magazine. After all, American readers have an insatiable appetite for news of the Duke and Duchess of Windsor, that glamorous couple whose love affair nearly brought the British monarchy to its knees five years earlier. What more intriguing backdrop for their romance than a wartime Caribbean paradise, a colonial playground for kingpins of ill-gotten empires?"--s
Keywords: Women journalists -- Fiction; Murder -- Fiction; Missing persons -- Fiction; Romance (Fiction); Historical fiction; Detective and mystery fiction